If You Think 9-Ending Prices Are Low, Think Again - Avichai Snir; Daniel Levy (ZBW – Leibniz Information Centre for Economics, 2019)
9-ending prices are a dominant feature of many retail settings, which according to the existing literature, is because consumers perceive them as being relatively low. Are 9-ending prices really lower than comparable non 9-ending prices? Surprisingly, the empirical evidence on this question is scarce. We use 8 years of weekly scanner price data with over 98 million price observations to document four findings. First, at the category level, 9-ending prices are usually higher, on average, than non 9-ending prices. Second, at the product level, in most cases, 9-ending prices are, on average, higher than prices with other endings. Third, sale prices are more likely to be non-9 ending than the corresponding regular prices. Fourth, among sale prices, 9-ending prices are often lower, on average, than comparable non 9-ending prices. The first three findings imply that although consumers may associate 9-ending prices with low prices, the data indicates otherwise. The fourth finding offers a possible explanation for this misperception. Retailers may be using 9-ending prices to draw consumers' attention to particularly large price cuts during sales, which perhaps conditions the shoppers to associate 9-ending prices with low prices.
Keywords: M30; M31; L11; L16; L81; D12; D22; D40; D90; D91; E31; 330; Behavioral Pricing; Psychological Prices; Price Perception; Image Effect; 9-Ending Prices; Price Points; Regular Prices; Sale Prices